Lesions of the commissural nucleus of the solitary tract reduce arterial pressure in spontaneously hypertensive rats - Sato, M. A.; Menani, José Vanderlei [UNESP]; Lopes, O. U.; Colombari, Eduardo [UNESP] (Lippincott Williams & Wilkins, 2001)
It has been suggested that increased sympathetic activity and arterial chemoreceptors are important for the high blood pressure in spontaneously hypertensive rats (SHR). Electrolytic lesions of the commissural nucleus of the solitary tract (commNTS) abolish (1) the cardiovascular responses to chemoreflex activation with potassium cyanide (KCN) in normotensive rats and (2) the hypertension that follows acute aortic baroreceptor denervation in rats. Therefore, in this study we investigated the effects of electrolytic lesions of the commNTS on basal mean arterial pressure (MAP), baroreflex, and chemoreflex in SHR and in normotensive control Wistar-Kyoto (WKY) and Wistar rats. CommNTS lesions elicited a dramatic fall in MAP to normal levels during the period of Study (from the first to fourth day following lesions) in SHR and almost no changes in WKY and Wistar rats. The pressor responses to chemoreflex activation with KCN tested in the days 1 and 4 after commNTS lesions were abolished in SHR and in normotensive strains. The reflex tachycardia induced by sodium nitroprusside was also attenuated in days 1 and 4 after commNTS lesions in SHR, WKY, and Wistar rats. The data suggest that the integrity of commNTS is important for the maintenance or high blood pressure in SHR and for the reflex responses dependent on sympathetic activation either in SHR or in normotensive strains.
Keywords: baroreceptors; chemoreceptors; solitary nucleus; rats, spontaneously hypertensive